Ecology and Infection Dynamics of Multi-Host Amdoparvoviral and Protoparvoviral Carnivore Pathogens - Marta Canuti; Melissa Todd; Paige Monteiro; Kalia Van Osch; Richard Weir; Helen Schwantje; Ann P. Britton; Andrew S. Lang (Pathogens, 2020)
Amdoparvovirus and Protoparvovirus are monophyletic viral genera that infect carnivores. We performed surveillance for and sequence analyses of parvoviruses in mustelids in insular British Columbia to investigate parvoviral maintenance and cross-species transmission among wildlife. Overall, 19.1% (49/256) of the tested animals were parvovirus-positive. Aleutian mink disease virus (AMDV) was more prevalent in mink (41.6%, 32/77) than martens (3.1%, 4/130), feline panleukopenia virus (FPV) was more prevalent in otters (27.3%, 6/22) than mink (5.2%, 4/77) or martens (2.3%, 3/130), and canine parvovirus 2 (CPV-2) was found in one mink, one otter, and zero ermines (N = 27). Viruses were endemic and bottleneck events, founder effects, and genetic drift generated regional lineages. We identified two local closely related AMDV lineages, one CPV-2 lineage, and five FPV lineages. Highly similar viruses were identified in different hosts, demonstrating cross-species transmission. The likelihood for cross-species transmission differed among viruses and some species likely represented dead-end spillover hosts. We suggest that there are principal maintenance hosts (otters for FPV, raccoons for CPV-2/FPV, mink for AMDV) that enable viral persistence and serve as sources for other susceptible species. In this multi-host system, viral and host factors affect viral persistence and distribution, shaping parvoviral ecology and evolution, with implications for insular carnivore conservation.